Lithium-conducting covalent-organic-frameworks as artificial solid-electrolyte-interphase on silicon anode for high performance lithium ion batteries. (June 2020) - Ai, Qing; Fang, Qiyi; Liang, Jia; Xu, Xinyu; Zhai, Tianshu; Gao, Guanhui; Guo, Hua; Han, Guifang; Ci, Lijie; Lou, Jun
Abstract: In this paper, we employ lithium-conducting covalent-organic-framework (COF) as the coating layer for silicon (Si) nanoparticles, which serve as artificial solid electrolyte interphase (SEI) for Si electrode. The COF coating layer reduces the electrolyte decomposition, thus the coulombic efficiency (CE) and cycling stability of the Si electrodes are dramatically improved. Additionally, the superior lithium–ion conductivity of COF can enhance the lithium-ion transportation kinetics of Si electrode. COF coated Si presented a high specific capacity of 1864 mAh g −1 at a high current density of 2000 mA g −1 and high capacity retention of more than 60% after 1000 cycles. Highlights: Lithium-conducting COF was grown on the surface of Si nanoparticles and served as artificial SEI layer. COF layer can reduce the electrolyte decomposition, improving the CE and cycling stability of Si anode. COF can enhance the lithium-ion transportation in Si anode, leading to the significant improvement of rate capability.